Crestal Incision Vs Plus Incision In Healing Of Gingival Collar In Second Stage Implant Surgery: A Comparative Study - Khuba Chavan, Arthi; V Naphade, Milind; Dwarkadas Adwani, Nitin; Vijay Gulhane, Shreyash; Sudhakar Mandaogade, Sanika; Vinit Mahure, Ishani (Journal of Neonatal Surgery, 2025)
Aim: To compare the effectiveness of crestal incision versus plus (+) incision techniques in the healing of the gingival collar during second-stage dental implant surgery, with particular focus on soft tissue contour, gingival health, and esthetic outcome. Materials and methods: A retrospective study was conducted to evaluate the impact of different incision techniques on gingival papilla height around single implants in the esthetic zone. The study included 50 patients (25 males, 25 females) aged 19–60 years. Papillae that met the strict inclusion criteria, which required healthy, functioning implants adjacent to natural teeth, thick gingival biotype (>1 mm), appropriate spacing (2.5–4 mm), and consistent surgical execution by a single operator. Patients with systemic diseases, poor implant positioning, active oral inflammation, smoking habits, or oral parafunctions were excluded. Data analysis was done using SSPS software. Results: In this study, a total of 50 patients were equally divided into two groups to compare the effects of crestal and plus incision techniques during second-stage implant surgery. The demographic and clinical characteristics were comparable between the two groups. The mean age in Group A (Crestal Incision) was 38.7 ± 10.4 years, while in Group B (Plus Incision) it was 39.2 ± 11.1 years. Gender distribution was similar, with 14 males and 11 females in Group A, and 13 males and 12 females in Group B. The implant placement locations were nearly balanced, with 16 maxillary and 9 mandibular implants in Group A and 15 maxillary and 10 mandibular in Group B. A majority of patients in both groups had a thick gingival biotype (17 in Group A and 18 in Group B). The mean duration since implant placement was also similar between the groups, being 7.2 ± 1.1 months in Group A and 7.4 ± 1.3 months in Group B. Conclusion: The plus incision technique in second-stage implant surgery showed better soft tissue healing and papilla preservation than the crestal incision, though further research with larger sample sizes is needed to confirm these findings.